Solidity Programming Essentials A beginner's guide to build smart contracts for Ethereum and blockchain - Modi, Ritesh (Packt Publishing Ltd, 2018)
Solidity is a new contract-oriented programming language popular for creating smart contracts and distributed applications. Writing smart contracts targeting Ethereum and other blockchain platforms is an emerging skill. This book will enable you to write robust, secure, object-oriented contracts that extend blockchain with business functionality
Description based on publisher supplied metadata and other sources
Keywords: Bitcoin; Electronic commerce; Electronic funds transfers